Bilateral Interactions in the Mouse Dorsal Inferior Colliculus Enhance the Ipsilateral Neuronal Responses and Binaural Hearing - Liu, Yun; Li, Yan; Peng, Yunyi; Yu, Haipeng; Xiao, Zhongju (Frontiers in Physiology, 2022)
The inferior colliculus (IC) is a critical centre for the binaural processing of auditory information. However, previous studies have mainly focused on the central nucleus of the inferior colliculus (ICC), and less is known about the dorsal nucleus of the inferior colliculus (ICD). Here, we first examined the characteristics of the neuronal responses in the mouse ICD and compared them with those in the ICC under binaural and monaural conditions using in vivo loose-patch recordings. ICD neurons exhibited stronger responses at ipsilateral sound stimulation and better binaural summation than those of ICC neurons, which indicated a role for the ICD in binaural hearing integration. According to the abundant interactions between bilateral ICDs detected using retrograde virus tracing, we further studied the effect of unilateral ICD silencing on the contralateral ICD. After lidocaine was applied, the responses of some ICD neurons (13/26), especially those to ipsilateral auditory stimuli, decreased. Using whole-cell recording and optogenetic methods, we investigated the underlying neuronal circuits and synaptic mechanisms of binaural auditory information processing in the ICD. The unilateral ICD provides both excitatory and inhibitory projections to the opposite ICD, and the advantaged excitatory inputs may be responsible for the enhanced ipsilateral responses and binaural summation of ICD neurons. Based on these results, the contralateral ICD might modulate the ipsilateral responses of the neuron and binaural hearing.